Climate-induced disasters in the Asia-Pacific region response, recovery, adaptation - Neef, Andreas; Pauli, Natasha (Community, Environment and Disaster Risk Management Ser., 2020)
In this volume, contributors look at response, recovery and adaptation to climate-induced disasters, in Asia-Pacific - the world's most disaster-prone region. Chapters examine case studies from Cambodia, Fiji, Solomon Islands and Samoa.